To save a life [videorecordings] - Heartshaper Video (Philippines : Lighthouse Educational Corp., 2011)
To save a life is... and lonely.
General audience.
Keywords: Christian life $1 (BDrama.s -- Suicide prevention $1 (BDrama.s